2018
DOI: 10.3389/fphar.2018.00092
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin Increases Cisplatin-Induced Apoptosis and Autophagy to Overcome Cisplatin Resistance in Non-small Cell Lung Cancer via ERK/p53 and c-met/AKT Signaling Pathways

Abstract: Cisplatin, as the first-line anti-tumor agent, is widely used for treatment of a variety of malignancies including non-small cell lung cancer (NSCLC). However, the acquired resistance has been a major obstacle for the clinical application. Scutellarin is a active flavone extracted from Erigeron breviscapus Hand-Mazz that has been shown to exhibit anticancer activities on various types of tumors. Here, we reported that scutellarin was capable of sensitizing A549/DDP cells to cisplatin by enhancing apoptosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 48 publications
3
42
0
Order By: Relevance
“…Many previous studies mainly focused on reactivating pro-apoptotic signals to enhance cell sensitivity to cisplatin (Rudin et al, 2003;Weir et al, 2007;Sun et al, 2018). The present study mimicked the generating process of cell resistance to cisplatin in vitro.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Many previous studies mainly focused on reactivating pro-apoptotic signals to enhance cell sensitivity to cisplatin (Rudin et al, 2003;Weir et al, 2007;Sun et al, 2018). The present study mimicked the generating process of cell resistance to cisplatin in vitro.…”
Section: Discussionmentioning
confidence: 65%
“…However, studies have shown that despite DNA damage, the signals promoting cell death are not sufficiently activated, which is partly due to mutations or downregulation of signaling molecules that drive cell death and also due to upregulation of signaling molecules preventing cell death. Many previous studies mainly focused on reactivating pro-apoptotic signals to enhance cell sensitivity to cisplatin (Rudin et al, 2003;Weir et al, 2007;Sun et al, 2018). Although some improvements of cell sensitivity to anti-cancer drugs have been made by promoting apoptosis, many cancer cells still show strong resistance to anti-cancer drugs through some undefined mechanisms, especially in clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al . reported that SCU enhanced cisplatin‐induces apoptosis and autophagy via the extracellular signal‐regulated kinase (ERK)/P53 or c‐met/AKT signaling pathways . This group also revealed that SCU induces apoptosis and autophagy in NSCLC cells through ERK1/2 and AKT signaling pathways in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 89%
“…20,21 Sun et al reported that SCU enhanced cisplatin-induces apoptosis and autophagy via the extracellular signal-regulated kinase (ERK)/P53 or c-met/AKT signaling pathways. 22 This group also revealed that SCU induces apoptosis and autophagy in NSCLC cells through ERK1/2 and AKT signaling pathways in vitro and in vivo. 23 Deng et al showed that SCU inhibits human renal cancer cell proliferation and migration via upregulation of phosphatase and tensin homolog, 24 while Ke et al reported that SCU effectively inhibits hepatocellular carcinoma metastasis in vivo and the migration and invasion of hepatocellular carcinoma cells in vitro.…”
Section: Discussionmentioning
confidence: 96%
“…DDP exerts cytotoxicity mainly by triggering cell apoptosis [ 20 ]. In embryonal carcinoma and lung cancer, drugs sensitize tumor cells to DDP by enhancing DDP-induced apoptosis [ 21 , 22 ]. Two main apoptotic pathways are involved in the cytotoxic agents-mediated apoptosis: the intrinsic and extrinsic pathways.…”
Section: Discussionmentioning
confidence: 99%